A Critical Review on the Book Principles of Parthian History - Farshid Naderi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Our awareness of Parthian Iran has been growing in recent decades. The concise but prolific book Principles of Parthian History by German archaeologist Klaus Schipmann was published in 1980. The main issue of this article is the content and form critique of the book and the views of its author. The book is reviewed based on analytical and critical methods. The chapter on political history, especially its political and legal analysis in the report on relations between Rome and Iran, is one of the brilliant chapters and a turning point of the book. The annoying tightness of the social, artistic, and economic sectors and the author's refusal to provide additional information and explanations are among the book's weaknesses. Other shortcomings of the book include the lack of images, the lack of related maps, and the author's refusal to provide excerpts from the text of coins, inscriptions, and written sources. The book has a high-quality typeface, page layout, and binding. In the field of translation, in addition to the difficult and sometimes formal prose of the translator and some errors in the names of the persons, some vague equations as well as the incorrect chronology of events, the book receives an acceptable score.